The prevalence of radiographic and MRI-defined patellofemoral osteoarthritis and structural pathology: a systematic review and meta-analysis. Issue 16 (29th April 2017) - Hart, Harvi F; Stefanik, Joshua J; Wyndow, Narelle; Machotka, Zuzana; Crossley, Kay M
Abstract : Background: Patellofemoral osteoarthritis (PF OA) is more prevalent than previously thought and contributes to patient's suffering from knee OA. Synthesis of prevalence data can provide estimates of the burden of PF OA. Objective: This study aims to conduct a systematic review and meta-analysis on the prevalence of PF OA and structural damage based on radiography and MRI studies in different populations. Methods: We searched six electronic databases and reference lists of relevant cross-sectional and observational studies reporting the prevalence of PF OA. Two independent reviewers appraised methodological quality. Where possible, data were pooled using the following categories: radiography and MRI studies. Results: Eighty-five studies that reported the prevalence of patellofemoral OA and structural damage were included in this systematic review. Meta-analysis revealed a high prevalence of radiographic PF OA in knee pain or symptomatic knee OA (43%), radiographic knee OA or at risk of developing OA (48%) and radiographic and symptomatic knee OA (57%) cohorts. The MRI-defined structural PF damage in knee pain or symptomatic population was 32% and 52% based on bone marrow lesion and cartilage defect, respectively. Conclusion: One half of people with knee pain or radiographic OA have patellofemoral involvement. Prevalence of MRI findings was high in symptomatic and asymptomatic population. These pooled data and the variability found can provide evidence for future research addressing risk factors and treatments for PF OA. Trial registration number: PROSPERO systematic review protocol (CRD42016035649).